Analysis of the Impact of COVID-19 Pandemic on Trade and Economy of the Coastal Communities of Kenjeran Village, Surabaya Using the Fault Tree Analysis (FTA) Method - Wirandoro, Hario Bagoes; Pratikto, Widi Agoes; Silvianita, Silvianita (Pusat Publikasi Ilmiah Institut Teknologi Sepuluh Nopember, 2022)
The coastal area as a densely populated area with high socioeconomic activity is currently experiencing impacts in various sectors due to the COVID-19 virus outbreak. However, the efforts to minimize the impact of the pandemic are still general and have not taken consider the conditions of communities in coastal areas. This analysis aims to determine the factors that cause the coastal community of Kenjeran to experience a decline and a decrease in trade and economic activity and identify the probability during the COVID-19 pandemic. The method used in this analysis is Fault Tree Analysis (FTA). The result shows that the main factors causing the decline are decreased fish sales, decreased community income, decreased activity at sea, and decreased activity of traders in the market with the probability factor of 0.2494 or 24%. Mitigation recommendations for the coastal community of Kenjeran Beach are a collaboration between the fishers and the policy of cooperation between the trade office and the marine service to conduct clustering for fishers so that they can supply scarcity of marine fish and limited marine product, also monitoring the health protocols with the swab and rapid tests for traders by permanent health service